The rise of digisexuality: therapeutic challenges and possibilities. Issue 3 (2nd October 2017) - McArthur, Neil; Twist, Markie L. C.
ABSTRACT: Radical new sexual technologies, which we term "digisexualities, " are here. As these technologies advance, their adoption will grow, and many people may come to identify themselves as "digisexuals" – people whose primary sexual identity comes through the use of technology. Researchers have found that both lay people and clinicians have mixed feelings about digisexualities. Clinicians must be prepared for the challenges and benefits associated with the adoption of such sexual technologies. In order to remain ethical and viable, clinicians need to be prepared to work with clients participating in digisexualities. However, many practitioners are unfamiliar with such technologies, as well as the social, legal, and ethical implications. Guidelines for helping individuals and relational systems make informed choices regarding participation in technology-based activities of any kind, let alone ones of a sexual nature, are few and far between. Thus, a framework for understanding the nature of digisexuality and how to approach it is imperative.